The role of Altruism and Empathy in anticipating the Attitude toward Organ Donation among Nurses in Intensive Care Units of Qazvin: A Cross-Sectional Study - L. Yekefallah; L. Dehghankar; M. Taherkhani; M. Ranjbaran (Вестник трансплантологии и искусственных органов)
Aim: Nurses, especially nurses in ICUs play an important role in organ donation; their performance in relation to their role is more affected by their attitude in this regard, identification of effective factors on the positive attitude of nurses towards organ donation is essential. This study was conducted aimed to determine the empathy and altruism with the nurses’ attitudes in intensive care unit towards organ donation and brain death. Methods. In this cross-sectional study, which was conducted in 2019, 222 nurses from intensive care unit were selected by stratified random sampling. For collecting data the questionnaires of altruism, empathy and attitude toward organ donation were completed by nurses. Data was analyzed using pearson correlation, multiple linear regression. Results. There was a significant correlation between altruism (p < 0.001, r = 0.24) and its components (anonymous prosocial behaviors (r = 0.33, p < 0.001), emotional prosocial behaviors (r = 0.14, p = 0.03), dire prosocial behaviors (r = 0.14, p = 0.03) and compliant prosocial behaviors (r = 0.21 and p = 0.001)) with attitudes and also between empathy (r = 0.04, r = 0.13), perspective taking component (p = 0.02, r = 0.152) and imaginary empathy (r = 0.14, p = 0.03) with nurses’ attitudes. The components of anonymous prosocial behaviors in altruism (p < 0.0001), gender (p = 0.007) and having organ donation card (p = 0.012) are positive predictors of nurses’ attitudes towards organ donation. Conclusion. The results showed that altruism and having organ donation card were two of the most important factors in the tendency of nurses to organ donation. Therefore, the implementation of educational programs regarding changing nurse’s attitude in order to increase the sense of altruism and empathy about organ donation is necessary. By strengthening the sense of altruism and empathy in the family of brain death patients, they can be helped to decide on donate their patient’s organ with more certainty.